The changing face of higher education in a widening participation context during the Covid-19 pandemic - Heather Thaxter (Educational Futures)
The following opinion piece is an extended version of a discussion article recently published in Academia Letters (Thaxter, Article 2730, 2021). As a reflective practitioner, my original intention was to record my observations of four cohorts of humanities undergraduates during the first year of the Covid-19 pandemic (March 2020-May 2021) to determine the extent to which teaching and learning was affected during the move to fully online delivery. I was also interested in the potential implications for engagement and achievement should this situation continue, especially considering the distinct student profile: students are primarily recruited through the Widening Participation Strategy (WPS). The English degree was already delivered as a blended learning model so undergraduates were familiar with various modes of online teaching and learning; however, behavioural changes were noted which subsequently affected group dynamics. The psychological impact, which manifested itself primarily in observable heightened anxiety, was of significant concern. Could the increase in the frequency of participatory telecopresence be a factor, and, if so, what theoretical approach could be applied to critically analyse these observations? Likewise, does the distinct student profile contribute to these observable changes in any way? As the behavioural changes seemed to be linked to the expectation to be ‘on-camera’ in an altered learning environment, I applied Erving Goffman’s Face Theory and Henri Lefebvre’s Production of Space Theory in an attempt to critically analyse these observations and inform pedagogy, going forward.